Peningkatan Pendapatan Pasif Melalui Penyewaan Tanah Ke Pihak Lain - Stefanus H. Gusti Ma; Maria S. Ngguwa (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
This research aims to analyze strategies for increasing passive income through renting land to other parties and its economic impact on land owners. Using qualitative descriptive methods, this research involved 5 respondents who were land owners who rented out their land in various areas in Ende Regency for the 2015-2025 period. Data collection techniques were carried out through in-depth interviews, observation and document analysis. The research results show that renting land can increase passive income by an average of 15-30% of the total assets owned. Factors that influence success include strategic location, type of land use, contract duration, and relationship management with tenants. The main challenges faced are fluctuations in rental prices, risk of property damage, and legal aspects. This research recommends the importance of strategic planning, diversifying land portfolios, and strengthening legal aspects in rental contracts to maximize passive income potential.